The Fulfilment Service Provider in Product Safety and Liability: A Silver Bullet for the Enhancement of Safety and Compensation in E-Commerce, or a Leap of Faith? - Gitta Veldt (European Journal of Risk Regulation)
The European legislator has included the fulfilment service provider (FSP) in European product safety legislation as a new responsible economic operator (EO) in e-commerce for instances where no other EO is based in the European Union. As a matter of coherency, this adjusted personal scope of product safety law will likely be mirrored in a revised product liability directive. This article explores to what extent the aims and expectations of European legislator with respect to these legal changes (law in the books) align with the perceptions of FSPs and legal advisors in the field (law in action). This is done by means of a legal analysis of the goals and envisioned effects of these changes as well as a semi-structured interview study on how FSPs and legal advisors in the field perceive this new role, responsibility, and liability. The findings provide indications that product safety law currently in force might not (yet) lead to the desired effects. The findings also make us question the extent to which victim compensation is actually improved by the proposed adjustment of the personal scope of the product liability directive.